Self-enforcing trade agreements: Evidence from time-varying trade policy - Chad P. Bown; Meredith A. Crowley (Federal Reserve Bank of Chicago, 2012)
The Bagwell and Staiger (1990) theory of cooperative trade agreements predicts new tariffs (i) increase with imports, (ii) increase with the inverse of the sum of the import demand and export supply elasticities, and (iii) decrease with the variance of imports. We find US import policy during 1997-2006 to be consistent with this theory. A one standard deviation increase in import growth, the inverse of the sum of the import demand and export supply elasticity, and the standard deviation of import growth changes the probability that the US imposes an antidumping tariff by 35%, by 88%, and by -76%, respectively.
Keywords: F12; F13; 330; trade agreements; terms of trade; anti-dumping; safeguards; WTO